Autoimmune disease-associated lymphomas: research progress and review - Chen, Chengqian; Guo, Wei; Zhao, Yangzhi; Wang, Xingtong; Li, Jia; Zhang, Ying; Li, Zhaoxia; Wang, Haotian; Bai, Ou (Frontiers in Immunology, 2026)
Autoimmune diseases (ADs) are strongly associated with a significantly increased risk of lymphoma, with the standardised incidence ratio (SIR) markedly elevated in certain conditions, most notably in Sjögren’s disease (SjD) where an SIR as high as 18.8 has been reported. The risk is particularly prominent for diffuse large B-cell lymphoma (DLBCL) and mucosa-associated lymphoid tissue (MALT) lymphoma. This review systematically elucidates the epidemiological features, pathological mechanisms, risk factors, and therapeutic strategies of ADs-associated lymphomas. Epidemiological studies have confirmed strong associations between ADs such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and SjD with specific lymphoma subtypes, and these associations appear to be bidirectional. Core pathogenic mechanisms involve malignant transformation driven by the immune–inflammatory continuum: chronic antigenic stimulation and the inflammatory microenvironment result in regulatory cell (Treg/Breg) dysfunction, tertiary lymphoid structure (TLS) formation, and clonal evolution. Specific autoantibodies directly contribute to oncogenesis by interfering with intracellular signalling pathways, mimicking antigenic stimulation, and forming immune complexes, while infectious agents such as Epstein–Barr virus synergistically promote malignant transformation within immunosuppressive microenvironments. Risk factors encompass intrinsic disease features, treatment-related risks and gene–environment interactions. Clinical management must balance the dual imperatives of “controlling inflammation” and “minimising treatment-related risks”. Targeted therapies, such as rituximab and BTK inhibitors, as well as haematopoietic stem cell transplantation (HSCT), have offered hope, but prognosis remains profoundly influenced by baseline immune status. Future research should focus on risk stratification guided by multi-omics, the application of novel immunotherapies in the autoimmune setting, and the optimisation of multidisciplinary care models.